Residu Pestisida pada Tanaman Hortikultura (Studi Kasus di Desa Cihanjuang Rahayu Kecamatan Parongpong Kabupaten Bandung Barat) - Euis Amilia; Benny Joy; Sunardi Sunardi (Fakultas Pertanian Universitas Padjadjaran, 2016)
ABSTRACTResidue of Pesticides on Horticultural Crops (Case Study in Cihanjuang Rahayu Village, Parongpong District, West Bandung Regency)The purpose of this study was to investigate the type of residual concentrate of chlorpyrifos pesticides accumulated in horticultural crops, the impact of pesticide residues to the public health and daily intake assumption. This study used a quantitative approach to survey methods to know in depth about pesticide residues on horticultural crops where the data source consisted of primary data obtained from interviews and the results of chemical analysis and secondary data collected directly from some sources. In several types of insecticides used by farmers in Cihanjuang Rahayu village, there are kind of insecticides that did not recommended to control pests on broccoli. Based on the analysis of pesticide residues, residue results were obtained from four broccoli samples with 10%, 20%, 60% and 80% greater than the maximum residue limit. This suggests that the four samples tested contain harmful residues exceeding the maximum limit of 2 ppm residue. Health effects of pesticides on farmers included nausea, vomiting, dizziness and itching of the skin. The calculating results of intake assumption on the risk of health obtained the result of 1,505 g/day with the highest value of 4,014 g/day and the lowest risk was the amount of intake of 423 g/day. From the results of these calculations, it can be seen that the amount of consumption of vegetables and horticulture was having average risk to farmers as much as 1,505 g/day.Keywords: Residue, Pesticides, Horticulture, BroccoliABSTRAKTujuan penelitian ini yaitu untuk mengetahui jenis konsentrat residu pestisida klorpirifos yang terakumulasi pada tanaman hortikultura, dampak residu pestisida bagi masyarakat dan asumsi asupan beresiko kesehatan per hari. Penelitian menggunakan pendekatan metode survei bersifat kuantitatif dengan sumber data primer yang diperoleh dari hasil wawancara dan hasil analisis kimia serta data sekunder yang dikumpulkan secara langsung dari narasumber. Beberapa jenis insektisida yang digunakan oleh petani di Desa Cihanjuang Rahayu, Bandung Barat terdapat jenis insektisida yang tidak direkomendasikan untuk mengendalikan hama pada tanaman brokoli. Hasil analisis terhadap residu pestisida pada empat sampel tanaman brokoli diperoleh residu pada keempat sampel yang diuji dengan persentase 10%, 20%, 60% dan 82% dari batas maksimum residu. Dampak penggunaan pestisida terhadap kesehatan petani yaitu berupa mual-mual, muntah, pusing dan gatal-gatal pada kulit. Hasil perhitungan asumsi asupan beresiko kesehatan melalui analisis pemajanan diperoleh hasil 1.505 g/hari dengan nilai tertinggi 4.014 g/hari dan jumlah asupan beresiko terendah adalah 423 g/hari. Dari hasil perhitungan tersebut dapat diketahui bahwa jumlah konsumsi sayuran dan hortikultura rata-rata beresiko oleh para petani adalah sebesar 1.505 g/hari.Kata Kunci: Residu, Pestisida, Hortikultura, Brokoli